Multidimensional Quality of Life of Older Adults in South Africa - Rossouw, S; Greyling, T; Kopylova, N (Springer, 2022)
It is estimated that by 2050, the world population over the age of 65 will reach 1.5 billion. The United Nations predicts that the fastest growth will be in Africa, which suffers from extreme poverty and inequalities. Therefore, older people who play an essential role in African culture face significant well-being challenges. To mitigate these challenges and improve quality of life (QoL), we must first assess their well-being levels. Well-being is a multidimensional concept and needs a multidimensional measure. However, the dimensions that explain older people’s QoL differ from other age groups and between developed and developing countries. We construct a unique index applicable to Africa. We functionalised the index using the South African National Income Dynamic Study dataset. By applying the new index empirically, we determine the level of QoL of older adults. Additionally, we establish which dimensions explain the most variance signalling areas for policy intervention. Furthermore, analysing panel data allows us to follow older individuals’ well-being over time to determine the trend. Lastly, we analyse different demographic groups’ well-being to establish the most vulnerable. We find the dimensions that explain the most variance are household services, economic status, safety, mental and physical health. The well-being of older adults increased over time, likely due to policy interventions, and the most vulnerable group is black African women in traditional and farming areas. Other developing countries could adopt our QoL index to measure the well-being of older people at a micro-level.
Keywords: Quality of life; Older adults; Categorical principal component analysis; South Africa